PENERAPAN E-GOVERNMENT DALAM MENINGKATKAN PARTISIPASI PUBLIK DI DESA BINA BARU KECAMATAN KULO KABUPATEN SIDENRENG RAPPANG - Mutiah Khaerunnisa; Muhammad Rais Rahmat Razak; Haeruddin Syarifuddin (LPPM Universitas Abdurrab, 2025)
This study aims to provide an in-depth analysis of the implementation of e-government in enhancing public participation in Bina Baru Village, Kulo Sub-district, Sidenreng Rappang Regency. Employing a descriptive qualitative approach, data were collected through direct field observations, in-depth interviews with village officials and local residents, as well as a review of relevant policy documents. The findings reveal that existing e-government systems, particularly Siskeudes and the village website, remain focused on improving internal administrative efficiency and financial transparency rather than facilitating meaningful public participation. Key barriers identified include low levels of digital literacy, limited internet connectivity, inadequate technological facilities, and the absence of interactive features for citizen feedback or consultation. Analysis using the Technology Acceptance Model (TAM) and Arnstein’s Ladder of Citizen Participation demonstrates that participation is still limited to the informative and consultative levels. The study recommends developing more inclusive digital portals, implementing continuous digital literacy programs, and combining digital innovation with local deliberative traditions to strengthen rural community engagement.